Demographic Features of Idiopathic Macular Telangiectasia in Korean Patients - Kim, Sung Hyun; Oh, Jaeryung; Ahn, Soh-Eun; Park, Choul Yong; Oh, Jong-Hyun (Korean journal of ophthalmology, 2015)
To investigate the clinical and demographic features of idiopathic macular telangiectasia (MacTel) in Korean patients since the introduction of spectral domain optical coherence tomography (SD-OCT). We reviewed medical records of patients who were diagnosed with MacTel from 2009 to 2013. All patients underwent fluorescein angiography and SD-OCT and were classified as type 1 or type 2 according to the classification system proposed by Yannuzzi. Over a period of 5 years, 4 (18.2%) patients were diagnosed with type 1 MacTel and 18 (81.8%) patients were diagnosed with type 2 MacTel. All patients with type1 MacTel were male, and their mean age was 51 ± 8.6 years. Among patients with type 2 MacTel, 3 (16.7%) were male, 15 (83.3%) were female, and the mean age was 60 ± 13.6 years. Whereas all type 1 MacTel patients had either metamorphopsia or mild scotoma, of the 18 patients with type 2 MacTel, only 4 (22.2%) had those symptoms, 10 (55.6%) complained of only mild visual impairment, and the other 4 (22.2%) had no symptoms. Intraretinal cystoid spaces were observed in 26 (72.2%) of 36 eyes with type 2 MacTel by SD-OCT. These cystoid spaces had irregular boundaries and did not correspond to angiographic leakages. Type 2 MacTel was most common in the present study. The wider availability of SD-OCT may have contributed to the diagnosis of type 2 MacTel. Type 2 MacTel may be more prevalent than type 1 in Koreans, which corresponds to the results of Western countries.